“Wiyawi Ebi”: A Study of Kalinga Vocal Music from the Philippines - Kevin Catalon (Nota Bene)
The Philippines has faced marginalization due to its colonial history, hindering the development of a cohesive national identity and a representation in musicological discourse. Among the country’s many Indigenous groups, the Kalinga people of the Cordilleras region remain unheard even within their own country. Focusing on the Kalinga song “Wiyawi,” this study examines the lullaby’s cultural significance, musical structure, and tuning systems through an analysis of field recordings and transcriptions by Felicidad A. Prudente. Drawing on the ethnomusicological frameworks of Prudente, José Maceda, and Aaron Prior, this research produces a new transcription of the song, which further reveals the lullaby’s role in the context of Kalinga traditions. Collaboration with members of the Kalinga culture enriched this work, yielding a newly expanded set of lyrics to “Wiyawi.” Additionally, the new transcription provides insight into the Kalinga tuning system in vocal music by investigating scholarship on anhemitonic scales in instrumental music. This paper calls for further ethnomusicological research and fieldwork to emphasize the importance of preserving Indigenous music in global musicological discourse and ensure that the voices of the Kalinga people are heard and valued.